ABDUL LATIF: THE FORGOTTEN MERCHANT OF THE WESTERN COAST OF SUMATRA - ZUSNELI ZUBIR (Sriwijaya University Learning and Education International Conference, 2016)
Minangkabau merchant is a kind of typical entrepreneuship of Minangkabau closer equivalent to the concept of merchant rather than as an entrepreneur in terms of capitalist industry. Abdul Latif is a portrait of a Minangkabau merchant managed to build a business network through the shaft Malaya, India, Arabia, and Egypt. Business profits, channeled through the efforts evoke a sense of nationalism and encourage the modernization of Islam in West Sumatra, and the Nagari Koto Anau, in particular. However, the figure of entrepreneurs is not widely known, especially among the younger generation of Minangkabau. Who is Abdul Latif?, How to build world business? How to encourage modernization efforts and Islam in West Sumatra?